Stalinism Revisited (Central European University Press, 2022)
Deals with the period of takeover and of 'high Stalinism' in Eastern Europe (1945–1955). These years are considered to be fundamentally characterized by institutional and ideological transfers based upon the premise of radical transformism and of cultural revolution. Both a balance-sheet and a politico-historical synthesis that reflects the archival and thematic novelties which came about in the field of communism studies after 1989.